CHALLENGES IN DEVELOPING SPEECH-NORMATIVE COMPETENCE AMONG UZBEK EFL STUDENTS (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
This study examines the challenges in developing speech-normative competence among Uzbek learners of English as a Foreign Language (EFL). Speech-normative competence refers to the ability to use language appropriately according to grammatical, sociolinguistic, and communicative norms. Despite significant improvements in foreign language education in Uzbekistan, many learners still face difficulties in applying language norms in real-life communication. The research adopts a mixed-method approach, including classroom observations, questionnaires, and speaking task analysis conducted among 60 intermediate-level students. The findings reveal that students experience challenges related to limited exposure to authentic input, insufficient communicative practice, and overemphasis on grammar-based instruction. The study proposes methodological solutions such as communicative language teaching (CLT), task-based learning (TBL), and increased use of authentic materials. The results contribute to improving teaching practices and enhancing communicative competence among EFL learners.